2020
DOI: 10.3390/ani10060994
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genomic Characteristics and Selective Signals in a Du’an Goat Flock

Abstract: The Du’an goat is one of the most important farm animals in the Guangxi Autonomous Region of China, but the genetic basis underlying its adaptive traits has still not been investigated. Firstly, in this study, the genomes of 15 Du’an goats from a breeding farm were sequenced (mean depth: 9.50X) to analyze the patterns of genetic variation. A comparable diversity (17.3 million single nucleotide polymorphisms and 2.1 million indels) was observed to be associated with a lower runs of homozygosity-based inbreeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Particularly, the variations in the inbreeding coefficients across JC goats mainly result from inbreeding events during the past 100 generations, also supported by the relatively small N e in these generations. Moreover, the historical trend in N e of JC goats agreed with those in other Chinese native goat breeds [ 40 , 54 ], mainly attributed to a lack of high commercial values of these breeds and changes in the economy in China. Consistent with previous studies in livestock [ 15 , 53 ], we also found a high correlation between F ROH and F HOM because both measures capture whole-genome homozygosity irrespective of the allele frequency at different genomic positions.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Particularly, the variations in the inbreeding coefficients across JC goats mainly result from inbreeding events during the past 100 generations, also supported by the relatively small N e in these generations. Moreover, the historical trend in N e of JC goats agreed with those in other Chinese native goat breeds [ 40 , 54 ], mainly attributed to a lack of high commercial values of these breeds and changes in the economy in China. Consistent with previous studies in livestock [ 15 , 53 ], we also found a high correlation between F ROH and F HOM because both measures capture whole-genome homozygosity irrespective of the allele frequency at different genomic positions.…”
Section: Discussionsupporting
confidence: 54%
“…Here, we identified several selected genes related to reproduction, such as KIT and KHDRBS2 . The KIT and its ligand (i.e., KITLG ), two well-known pigmentation genes in livestock, are common selection signals in many different goat [ 16 , 18 , 54 , 60 , 61 ] and sheep populations [ 18 , 62 ], which may imply their pleiotropic effects. We previously identified a selection signal encompassing KHDRBS2 in Meigu goats [ 63 ], which are known for their high fertility and precocious puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low inbreeding indicates higher levels of heterozygosity, which are more linked to genetic variation and improved adaptability to harsh environmental situations ( Makina et al, 2015a ; Abondio et al, 2022 ). The average number of ROHs in Xiangdong goats is relatively high, which may provide a reference for the breeding and conservation of these goats since animals with high levels of ROH could be excluded or assigned lower priority for mating to minimize the loss of genetic diversity ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IL1R1 gene is regarded as a candidate gene for the induction of autoimmune responses in goats ( Amiri Ghanatsaman et al, 2023 ); similarly, the IL7 gene is the top signaling gene for the induction of immunological responses in the worldwide goat population ( Crisà et al, 2016 ). Among milk production- and composition-related attributes, SPP1 ( Li et al, 2020 ), TLL1 and ERBB4 , which are related to colostrum and lactation regulation ( Chen et al, 2020 ), respectively, have been studied previously. Additionally, genes involved in the response to environmental stressors and thermoregulation in the Du’an goat flock ( Chen et al, 2020 ) were also found to be the most positively selected genes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Gene ontology results in wild goats showed that these genes were related to biological pathways of proteoglycans in cancer, phosphotransferase activity, alcohol group as acceptor, protein phosphorylation, and T‐cell receptor signaling pathway. In a study conducted by Chen et al (2020) to identify signatures of selection in the Du'an Goat, a domestic breed in south China, the results showed that the proteoglycans in cancer pathway was under selection. Also, in another study that was done on a Spanish dairy breed, Murciano‐Granadina goats, proteoglycans in cancer pathway was under selection (Guan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%